On grief and griefbots - Voinea, C (Cambridge University Press, 2024)
Griefbots are chatbots designed to assist individuals in coping with the loss of a loved one by offering a digital replica of the departed. Navigating grief is a deeply transformative and vulnerable journey intricately tied to one's well-being. Do griefbots aid in the grieving process, or do they complicate it? To address these questions, this article blends insights from philosophy and neuroscience to explore the nature of grief as a means to clarify the ethical dimensions surrounding the use of griefbots.